2006
DOI: 10.1007/s10620-006-8010-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Damage in Strongyloidiasis: The Imbalance Between Cell Death and Proliferation

Abstract: Strongyloidiasis is an endemic tropical parasitosis caused by Strongyloides stercoralis that also affects immigrants in nontropical countries. The nematode colonizes the duodenum and upper jejunum, inducing mucosal alterations. Because integrity is essential for a functional barrier, we aimed to study apoptosis and proliferation in the small bowel epithelium infected with S. stercoralis. We evaluated 23 patients and 17 controls. Apoptotic cells were detected by TUNEL and M30 immunolabelling, whereas proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Suarez and Sanchez [19] confirmed that plasma cell infiltration, villous atrophy and severe duodenitis were the characteristics of severe strongyloidiasis. A recent study clearly demonstrated that strongyloidiasis disrupted epithelial kinetics in the human small intestine by the induction of apoptosis and inhibition of cell proliferation, thereby resulting in villous atrophy and impaired barrier function [17] . Our observations disclosed that endoscopic findings of duodenitis were more severe in the patients whose biopsies were positive for larvae than in those with negative biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suarez and Sanchez [19] confirmed that plasma cell infiltration, villous atrophy and severe duodenitis were the characteristics of severe strongyloidiasis. A recent study clearly demonstrated that strongyloidiasis disrupted epithelial kinetics in the human small intestine by the induction of apoptosis and inhibition of cell proliferation, thereby resulting in villous atrophy and impaired barrier function [17] . Our observations disclosed that endoscopic findings of duodenitis were more severe in the patients whose biopsies were positive for larvae than in those with negative biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…However, pathognomonic findings are apparently not evident [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Our present study confirmed the aforementioned frequent findings.…”
Section: P R I O R R E P O R T S H a V E I N D I C A T E D T H A T F mentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathological analyses of human intestines have shown that S. stercoralis eggs and adult females colonise the duodenum and upper jejunum. Studies have also demonstrated the presence of oedema, duodenal villous atrophy, and crypt hyperplasia with disrupted epithelium due to the inhibition of cell proliferation and apoptosis (Coutinho et al, 2006;Werneck-Silva et al, 2006). Surface damage, ulceration, an increase in mucus secretion and functional changes in the intestine have also been reported.…”
Section: Acute Infectionmentioning
confidence: 98%